DIAGNOSTIC VALUE OF ASCITIC FLUID FIBRONECTIN CONCENTRATION IN DIFFERANTIATION CIRRHOTIC AND MALIGNANT ASCITES - Abdullah SONSUZ; Hakan ŞENTÜRK; Sebati ÖZDEMİR; Sait KARAKURT; Perihan AKIN; Muzaffer GÜRAKAR (Turkish Journal of Gastroenterology, 2020)
-